2019
DOI: 10.1016/j.resp.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular advancement reveals long-term suppression of breathing discomfort in patients with obstructive sleep apnea syndrome

Abstract: Isabelle Arnulf, et al.. Mandibular advancement reveals long-term suppression of breathing discomfort in patients with obstructive sleep apnea syndrome. Respiratory Physiology and Neurobiology, Elsevier, 2019, 263, pp. AbstractObstructive sleep apnoea syndrome (OSAS) patients do not report breathing discomfort in spite of abnormal upper airway mechanics. We studied respiratory sensations in OSAS patients without and with mandibular advancement device (MAD).Fifty-seven moderate to severe non obese OSAS patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Patients suffering from obstructive sleep apneas (OSA) do not complain of dyspnea during awake resting breathing, notwithstanding abnormalities in upper airway mechanics representing an inspiratory load (Attali et al., 2019 ). Yet, despite this absence of respiratory complaints, the placement of a mandibular advancement device (MAD), known to improve upper airway mechanics (Gakwaya et al., 2014 ), can lead to a sense of improved respiratory comfort (Attali et al., 2019 ), hereafter termed “pseudo‐relief”. The intensity of this sensation correlates with the degree of mechanical improvement brought about by the MAD (Attali et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients suffering from obstructive sleep apneas (OSA) do not complain of dyspnea during awake resting breathing, notwithstanding abnormalities in upper airway mechanics representing an inspiratory load (Attali et al., 2019 ). Yet, despite this absence of respiratory complaints, the placement of a mandibular advancement device (MAD), known to improve upper airway mechanics (Gakwaya et al., 2014 ), can lead to a sense of improved respiratory comfort (Attali et al., 2019 ), hereafter termed “pseudo‐relief”. The intensity of this sensation correlates with the degree of mechanical improvement brought about by the MAD (Attali et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…OSAS patients [30] remains putative and needs to be further explored. However, the present study showed that the proposed method could be integrated in routine clinical practice, because of the low dose of radiation delivered to the patient and an examination protocol that can easily be reproduced.…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 99%
“…The study also underlined that the maxillomandibular advancement surgery is a safe and very effective treatment option to OSAS. According to Attali et al 2019 [ 35 ], MAD revealed “latent dyspnea” related to the severity of upper airways mechanics abnormalities in OSAS patients. Similar findings were illustrated by Marty et al 2017 [ 36 ] stating that custom-fitted MAD improved respiratory and somnolence parameters, with response rates similar to those published in the literature with other devices.…”
Section: Discussionmentioning
confidence: 99%